No Long-Term Superiority of Cord-Derived PRP over Autologous PRP in Knee Osteoarthritis: A Prospective Cohort Study - Michele Coviello; Antonella Abate; Giuseppe Maccagnano; Alessandro Geronimo; Elio Caiaffa; Vittorio Nappi; Vincenzo Caiaffa; Giuseppe Solarino (Journal of Functional Morphology and Kinesiology, 2025)
Background: Knee osteoarthritis (OA) is a progressive joint disorder characterized by pain, stiffness, and functional impairment. Platelet-rich plasma (PRP) has been widely studied as a biological treatment for OA, with autologous PRP (A-PRP) being the most commonly used formulation. Recently, umbilical cord-derived PRP (C-PRP) has emerged as a potential alternative due to its hypothesized higher regenerative potential. However, evidence supporting its superiority over A-PRP remains limited. This study aims to compare the efficacy and safety of C-PRP and A-PRP in terms of pain relief and functional improvement over a 12-month follow-up period. Methods: This prospective cohort study included 84 patients with mild-to-moderate knee OA (Kellgren–Lawrence grades I–III), into two groups: 44 patients received a single intra-articular injection of C-PRP, and 40 received A-PRP. Pain and functional outcomes were assessed at baseline, 3, 6, 9, and 12 months using the Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Knee Injury and Osteoarthritis Outcome Score (KOOS). Statistical analysis was performed using the Mann–Whitney U, Exact Fisher test, repeated measures general linear model (GLM) and multivariate logistic regression. Results: Both C-PRP and A-PRP led to significant pain reduction and functional improvement over 12 months (p < 0.01 for both groups). Short-term analysis (3–6 months) showed slightly greater pain relief in the C-PRP group (VAS, p = 0.03 at 3 months), but this difference diminished at later time points. By 9 and 12 months, no significant differences were observed between the two groups in any clinical outcome measures (VAS, WOMAC, KOOS; p > 0.05). No serious adverse events were reported, and both treatments were well tolerated. Conclusions: This study found no long-term superiority of C-PRP over A-PRP in terms of pain relief or functional improvement in knee OA. While C-PRP showed a transient advantage in early pain relief, both treatments demonstrated similar clinical outcomes at 12 months. Given the limited scientific evidence supporting C-PRP and its higher logistical costs, A-PRP should remain the preferred PRP therapy for knee OA. Further randomized controlled trials with longer follow-up periods are needed to confirm these findings.